Handbook track greening. Design, implementation, maintenance. - (:unkn) unknown (DVV Media Group, Eurailpress, 2016)
Sustainable Track Greening requires the integration of knowledge and experience from railway track engineering and vegetation science. Selection of systems (track structure- and vegetation system), location specific conditions as well as maintenance effort are closely related and should be considered at large. The Handbook Track Greening offers a detailed overview and descriptions of established track structure systems and vegetation systems for light rail and tram schemes in Germany. It provides recommendations and practical guidance for the design, construction and maintenance of Green Track, focusing on technical principles. The book has been developed for light rail and tram schemes which are operated in accordance with the German BOStrab (Ordinance on the Construction and Operation of Street Railways) regulations however most of the technical principles apply to Green Track systems in general. Important legal aspects are indicated where applicable. This Handbook is the first to gather requirements, knowledge and experience on Track Greening and was compiled by the members of the Green Track Network ? experts from transit authorities, scientific institutes and manufacturers operating internationally. The Handbook is primarily aimed at experts with technical knowledge of track and vegetation systems but also at urban designers, city planners and beginners as reference guide.
Keywords: Öffentlicher Verkehr; ÖPNV; Straßenbahn; Gleisanlage; Technische Infrastruktur; Betrieb; Instandhaltung; Begrünung; Nachhaltigkeit; Fahrweg; Rasengleis